The Relations Between High Body Mass Index and Breast Cancer Characteristics - Salam Marouf , Shwan (Diyala Journal of Medicine, 2024)
Background: In the context of rising obesity rates globally, understanding the effect of high body mass index (BMI) on breast cancer characteristics is crucial. Previous research has hinted at associations between obesity and some specific features, such as tumor receptor status and axillary lymph node involvement. However, a comprehensive investigation into these relationships is essential for informing targeted interventions and advancing our understanding of breast cancer in the context of obesity. Objective: To investigate the relationship between high BMI and some key tumor characteristics such as hormone receptor status, HER2 receptor status, tumor grade, tumor size and axillary lymph node status. Patients and Methods: A retrospective analysis of the medical records of 186 female breast cancer patients treated at Rizgary Teaching Hospital's Oncology Department in Erbil City during the year 2021. Results: The study revealed a statistically significant association between elevated BMI and certain pivotal breast tumor characteristics, particularly HER2 receptor status. Additionally, obese individuals exhibited a significantly greater probability of having axillary lymph node-positive disease compared to their non-obese counterparts. Conclusion: This study establishes a noteworthy association between high BMI and some critical breast cancer characteristics, which may underscore the clinical relevance of body mass index in shaping breast cancer profiles.